Athens and the tyranny of a democratic state (2017)
Democracy, the celebrated symbol of socio-political success, seems the most popular legacy of Athens to the modern world. Yet, Athens also has a record of what has been seen as tyrannical use of power and ‘abuse of human right’ in her inter-state relations. Thucydides’ account of the Peloponnesian war (The History of the Peloponnesian War) has been a basis for the theory of political realism, ‘might is right’ which is used to explain the international aggression of the democratic Athens. Using an interpretive research approach, this paper takes some look at the Athenian path to democracy and particularly considers the Melian Dialogue, a passage in Thucydides’ work that enunciates the implications of political realism exemplified by the Athenians' treatment of the Melians. While political realism implies international anarchy when power and conflicting national interests set the standard of what is deemed right, a democratic government led by this code could also act tyrannically despite its leaders 'profession of justice and equity. Therefore, the paper concludes that since democracy is no limitation to morality and justice becoming subjective, when interests are at variance in domestic politics, such tendency in individuals or groups who constitute a democracy would continue to account for political instability.